The impact of maximal oxygen uptake (VO₂max) on athletic performance and health - a review - Julia Charkot; Wojciech Bieńkowski; bartlomiej kusy; Michał Bieńkowski; Mikołaj Charkot; Piotr Kucharczyk; Irmina Jaszczuk; Patrycja Retman (Quality in Sport, 2025)
Introduction and purpose: Maximal oxygen uptake (VO₂max) is a key indicator of aerobic capacity, widely used in sports science and clinical diagnostics. It reflects the functional efficiency of the cardiovascular, respiratory, and muscular systems. Given its relevance to physical performance and health risk prediction, VO₂max has become a central focus in exercise physiology and preventive medicine. The aim of this study is to review current literature on the physiological determinants, assessment methods, modifiability, and clinical implications of VO₂max.